When giants learn to dance - Kanter, Rosabeth Moss (Touchstone, 1990)
In this vital blueprint for career and corporate success, Professor Rosabeth moss Kanter shows exactly what it will take to resolve the dilemmas facing American business--and come out on top in the next decade.